363 VERTIGO, SENSORY COMPLAINTS, VISUAL AURA, AND MIGRAINE HEADACHES IN A LARGE FAMILY. (1st January 2006) - Kelley, L.; Baloh, R. W.; Jen, J.
Abstract : Purpose: To characterize the unusual clinical features within a large family with migraine and to explore possible genetic basis. Background: Migraine is a highly prevalent neurological disorder defined by repeated attacks of disabling throbbing headache with photo- and phono-phobia and variably associated with focal neurological deficits affecting visual, motor, and sensory function. The mechanism of migraine is not well understood but is thought to have a genetic component. Methods: The index patient presented to the UCLA Neurology Clinic for evaluation of recurrent vertigo, unusual sensory complaints, visual aura, and migraine headaches. We interviewed consenting relatives and obtained DNA samples for linkage analysis. Results: We identified affected individuals spanning five generations. Age of onset of symptoms, frequency, duration, resolution, and triggers were highly variable among subjects. Conclusion: The clinical presentation in this family is variable, with age- and gender-dependent penetrance. Recurrent vertigo and sensory complaints were temporally associated with migraine headaches and visual aura that are likely manifestations of migraine. Genetic linkage analysis is currently under way to identify candidate loci in this family with complicated migraine.